Like the back of my hand: Visual ERPs reveal a specific change detection mechanism for the bodily self. (January 2021) - Galigani, Mattia; Ronga, Irene; Fossataro, Carlotta; Bruno, Valentina; Castellani, Nicolò; Rossi Sebastiano, Alice; Forster, Bettina; Garbarini, Francesca
Abstract: The ability to identify our own body is considered a pivotal marker of self-awareness. Previous research demonstrated that subjects are more efficient in the recognition of images representing self rather than others' body effectors ( self-advantage ). Here, we verified whether, at an electrophysiological level, bodily-self recognition modulates change detection responses. In a first EEG experiment (discovery sample), event-related potentials (ERPs) were elicited by a pair of sequentially presented visual stimuli (vS1; vS2), representing either the self-hand or other people's hands. In a second EEG experiment (replicating sample), together with the previously described visual stimuli, also a familiar hand was presented. Participants were asked to decide whether vS2 was identical or different from vS1. Accuracy and response times were collected. In both experiments, results confirmed the presence of the self-advantage : participants responded faster and more accurately when the self-hand was presented. ERP results paralleled behavioral findings. Anytime the self-hand was presented, we observed significant change detection responses, with a larger N270 component for vS2 different rather than identical to vS1. Conversely, when the self-hand was not included, and even in response to the familiar hand in Experiment 2, we did not find any significant modulation of the change detection responses. Overall our findings, showing behavioral self-advantage and the selective modulation of N270 for the self-hand, support the existence of a specific mechanism devoted to bodily-self recognition, likely relying on the multimodal (visual and sensorimotor) dimension of the bodily-self representation. We propose that such a multimodal self-representation may activate the salience network, boosting change detection effects specifically for the self-hand.